Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Karyawan Pada Politeknik Negeri Jakarta - Retno Oktaviani; Aden Prawiro Sudarso (Manajemen Kreatif Jurnal, 2024)
The objective of this study is to explore the effects of Leadership Style and Organizational Culture on Employee Performance, either individually or in combination, within the State Polytechnic of Jakarta. A quantitative approach was adopted for this research, utilizing questionnaires to gather and analyze data. The participants comprised employees from the State Polytechnic of Jakarta, totaling 89 respondents. Analytical methods employed in this investigation included tests for validity, reliability, and normality, as well as tests for multicollinearity, autocorrelation, and heteroskedasticity. Additionally, analyses such as the correlation coefficient, simple linear regression, multiple linear regression, the coefficient of determination, and hypothesis testing were conducted, all facilitated through the use of SPSS 29, a statistical software designed for the social sciences, on a Windows platform. In testing individual hypotheses, results showed the calculated t for Leadership Style (5.239) significantly exceeded the critical t-value of 1.987, impacting Employee Performance significantly. However, the Organizational Culture's effect was not significant, as its t (0.706) was below 1.987. For combined hypotheses, the F-value of 47.444 far exceeded the critical value of 3.10, with significance below 0.001, leading to the rejection of H0 and acceptance of Ha, affirming that Leadership Style and Organizational Culture together significantly enhance Employee Performance at the State Polytechnic of Jakarta.